Rancang Bangun Alat Pemindah Drum Dengan Sistem Sudut Putar Sebagai Penuang - Mega Haryo Orlando; Tri Andi Setiawan; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Oil is very important in the manufacturing process, especially in the machining process, where the work process can minimize friction between components. Therefore, a lot of oil reserves are needed to be stored in the oil drum as a storage area for the 200 liter oil drum with the dimensions of the drum which has a diameter of 580mm and a height of 980mm. Therefore we need a tool to move the drum so that it is easy to move. However, existing tools still use load support during the transfer process. Because workers have to support heavy oil loads with the transfer work system by tilting and then pushing or pulling. This is considered unsafe because it can cause work accidents during the transfer process. The method used to manufacture this tool is Ulrich. The Ulrich method is a method of designing and developing products based on consumer needs. From the existing problems, a drum drive device with a maximum capacity of 200 kg was made and used a hanging system during the operational process, so that the drum moving process did not cause accidents to workers.